95% prevalence of abnormality on hip MRI in elite academy level rugby union: A clinical and imaging study of hip disorders. Issue 11 (November 2016) - Farrell, Garreth; McGrath, Frank; Hogan, Brian; Logan, Mark; Denvir, Karl; O'Connell, Brendan; Irwin, Ellevyn; Gissane, Conor; Wilson, Fiona
Abstract: Objectives: To identify the prevalence of hip disorders in elite level academy rugby union players using clinical and radiological investigation comparing findings to active controls. Design: Cross-sectional, controlled study. Methods: Participants were assessed clinically using validated questionnaire (HAGOS) and physical testing procedures. Active ROM of all hip movements were measured using a goniometer and hip-specific clinical tests including the FABER and the Thomas test examined functional hip motion. Physical tests were compared to age, gender and activity matched controls. The rugby-playing participants underwent dedicated non-arthrographic 3 T MRI imaging of the hip in axial oblique, sagittal and coronal planes to assess anatomical abnormality. Results: The rugby cohort had significantly reduced ROM of internal/external rotation, extension and FABER scores compared to the controls. Symptoms were reported by 65% of rugby players (HAGOS symptom score <89.3) versus 15% in controls. There was a 95% prevalence of abnormality on MRI (19 of 20 players); 80% of the elite rugby players had labral pathology, 55% had a cam deformity (45% left sided 30% right-sided) and 25% had either unilateral or bilateral chondral wear. Conclusions: The prevalence of abnormality on MRI of the hip is high in rugby players at 95% of study participants. The percentage reporting symptoms was lower at 65% of the cohort although this was significantly higher than (non-rugby) matched controls at 15% of participants. Rugby players demonstrated significantly reduced ROM of the hip compared to controls. Further prospective research is required to investigate the long term sequelae of these findings.